2020
DOI: 10.1002/rcm.8901
|View full text |Cite
|
Sign up to set email alerts
|

Effect of removal of organic material on stable isotope ratios in skeletal carbonate from taxonomic groups with complex mineralogies

Abstract: Rationale Stable oxygen and carbon isotope ratios are one of the most accurate ways of determining environmental changes in the past, which are used to predict future environmental change. Biogenic carbonates from marine organisms are the most common source of samples for stable isotope analysis. Before they are analyzed by mass spectrometry, any organic material is traditionally removed by one of three common pretreatment methods: roasting, bleaching, or with hydrogen peroxide at various strengths and duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 116 publications
(204 reference statements)
0
5
0
2
Order By: Relevance
“…For micropaleontological analysis, foraminifera were microfauna used as an indicator in this study. Analyzes were performed using standard methods, which using a solution of hydrogen peroxide (H2O2 3%) in sample preparation [26] to remove organic matters [27]. Samples were sieved by a 63 μm mesh, the residues oven-dried at <60°C, weighed and sieved into 63-150 μm and >150 μm size fractions [28].…”
Section: Methodsmentioning
confidence: 99%
“…For micropaleontological analysis, foraminifera were microfauna used as an indicator in this study. Analyzes were performed using standard methods, which using a solution of hydrogen peroxide (H2O2 3%) in sample preparation [26] to remove organic matters [27]. Samples were sieved by a 63 μm mesh, the residues oven-dried at <60°C, weighed and sieved into 63-150 μm and >150 μm size fractions [28].…”
Section: Methodsmentioning
confidence: 99%
“…We note that Eagle et al (2010) found no effect of pre-treatment on clumped isotope analyses of enamel but found an effect on analyses of dentine, suggesting that organic-rich apatites could be significantly affected by sample pre-treatment. Because we measured organic-poor enamel in this study, we follow the recommendations of Eagle et al (2010), Key et al (2020), Löffler et al (2019), andWacker et al (2016) and opt not to pre-treat apatite samples. Another source of uncertainty in paleothermometry of bioapatites involves animal behavior and seasonal cycles.…”
Section: Considerations For Apatite As a Paleothermometermentioning
confidence: 99%
“…Organic removal, depending on the selected method (e.g. heating or peroxide digestion), has been shown to have a potential effect on stable isotope values (Key Jr et al, 2020), but no consistent effect directionality was identified. Diet is another potential factor influencing experimental results, but the isotopic composition of oxygen in diet is generally not reported in experimental studies and is not explicitly considered here.…”
Section: Introductionmentioning
confidence: 99%